Trastornos alimentarios en los/as adolescentes del Colegio Particular Juan Montalvo - Chuquirima Ajila, María Elena (2015)
This research is called eating disorders in / as particularly teenagers Colegio Juan Montalvo, whose goal is to characterize the population of adolescents with eating disorders in that school, to which has been theoretically substantiated the problem of eating disorders in adolescents, their psychosocial profile and the impact they produce on their mental health, in addition to this behavior and the reasons for the intake of diet pills, diuretics, laxatives, among which was evaluated excel moments of anguish, despair and problems that seemingly have no solution and welfare gives them the act of eating and eating excessively to fill the emotional void in their lives, after the results developed an educational proposal focused on changing behaviors that lead teenagers to suffer of these disorders. A comprehensive analysis of the literature, in which different conceptualizations and approaches to problems in study, as did arise were: early disorders, cultural aspects of eating, anorexia and bulimia; Determining factors, consequences and characteristics according to the DSM IV criteria. Materials and methods, which allowed for field research, such as presented in the methodology, being a descriptive research and cross-section were used. An essential part of this thesis was the application of instruments teens first, second and third year of high school College of Particular Juan Montalvo consisting within the Eating Attitudes Test, questionnaire for dietary habits and patterns of weight (QEWP) allowing us to understand the behavior that adopt / learners to avoid gaining weight and stay slim, influenced by cultural standards of beauty and mass media. Checking level and conclusions we can rescue the behavior of adolescents to the adversities of life; thus we have the 75% take refuge in food for comfort, 100% of students have a habit of binge food in large quantity once a month, and then ingest diuretics, laxatives and diet pills to avoid gaining weight, or spend hours physical exercise and decreasing the feeling of guilt after excessive food intake, sufficient reasons I have developed an educational proposal that seeks to reduce the magnitude of the problem and to amend the precursor behavior disorders eating in adolescents. KEYWORDS: anorexia, bulimia, eating disorders, thinness, dieting.